Worries, coping strategies and well-being in adolescence: Highlights from HBSC study in Portugal - Matos, Margarida Gaspar de (2017)
The aim of this study was to understand adolescents’ worries and the strategies used to face them, and what makes them feel good. In this study, 3869 adolescents participated, of which 46.8% boys, attending grades 8 and 10, mean age 14.7 years, SD = 1.18, included in the Portuguese Health Behaviour in School-Aged Children survey 2014. In the first quantitative study, simple descriptive analyses and chi-squares were carried out and a regression model associated the intensity and frequency of worries with a decrease in perceived well-being; in a second qualitative study, content analysis was carried out regarding open questions about types of worries and ways to cope with worries and to increase well-being. It was clear that the majority of adolescents got worried frequently, part of them let worries interfere significantly with their lives, and that the best coping strategies are either trying to fix the problem or distraction. Family, peers (social support) and leisure time (distraction) are important factors in ensuring young people’s well-being. School seems to be ‘part of the problem’ but never ‘part of the solution’. Compared with previous studies, the economic crisis appears to be associated with the increased relevance of a new worry – economic and financial issues were not previously relevant. Gender and developmental/age differences were found. Although intensity and frequency of worries were significantly associated with lower perception of well-being, frequency had a higher association. The implications for health promotion interventions in families and in schools are discussed together with implications for public policies in the area of mental health.